Switchable Fabry–Perot filter for mid-infrared radiation. Issue 12 (26th September 2019) - Chodorow, U.; Mazur, R.; Morawiak, P.; Herman, J.; Harmata, P.; Martyniuk, P.
ABSTRACT: In this work, switchable liquid crystal infrared filter is presented. The tailored superfluorinated liquid crystal material exhibiting low parasitic absorption at the operating range has been used for the construction of the filter. The switching range as high as 300 nm is achieved by applying 18 V. The filter can operate continuously from 3.45 up to 3.75 μm. Graphical Abstract: